Effect of olive oil wastewaters polyphenols on chicken faecal and litter microbiota towards safe and effective waste valorisation - Debora Casagrande Pierantoni; Angela Conti; Chiara Ruspi; Leonardo Donati; Lorenzo Favaro; Laura Corte; Gianluigi Cardinali (Heliyon)
Olive oil wastewaters (OWW) represent a serious threat for the environment, prompting the development of various strategies to mitigate their toxic impact. In an attempt of sustainable agriculture and circular economy-based model, a promising alternative involves repurposing these wastes as a source of valuable compounds. This study explores the use of two polyphenol extracts obtained from OWW adopted as an alternative poultry feed additive in place of Vitamin E, commonly employed as the gold standard fodder antioxidant. The effects of these antioxidants on bacterial and fungal microbiota of chicken gut and litter were investigated, along with their influence on bacterial resistances to seven antibiotics from five different antimicrobial classes. Overall, the variation in Alpha and Beta diversity were found to be specific to each district, with the highest values observed in the litter. In this substrate, important for animal and workers health, polyphenols favoured fungi like Dipodascus, which negatively interact with pathogenic and opportunistic bacteria, while vitamin E produced the opposite outcome. Moreover, one of the two polyphenols employed decreased the amount of multi-antibiotic resistant bacteria (5 antimicrobial classes), compared to Vitamin E and control diet. Wheater polyphenols act negatively toward dangerous bacteria directly or through the positive interaction with competing fungal taxa will require additional studies. These findings imply that the use of OWW as a source of feed additives is not only beneficial for the environment but also to reduce the hazard of litter microbiota for animals and workers in poultry farming and in its use as a fertilizer.